2022
DOI: 10.1002/mds.29045
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin in Spinocerebellar Ataxia Type 2: Feasibility and Proof‐of‐Principle Issues from a Randomized Controlled Study

Abstract: Background Several pieces of evidence have shown the neurotrophic effect of erythropoietin (EPO) and its introduction in the therapeutic practice of neurological diseases. However, its usefulness in the treatment of spinocerebellar ataxia type 2 (SCA2) has not been proven despite the fact that it is endogenously reduced in these patients. Objective The study aims to investigate the safety, tolerability, and clinical effects of a nasally administered recombinant EPO in SCA2 patients. Methods Thirty‐four patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…To organize the information obtained from the articles and their relevance, tables were prepared in which preclinical studies (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) (Table 1) and clinical trials (24)(25)(26)(27)(28)(29)(30) (Table 2) were grouped.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To organize the information obtained from the articles and their relevance, tables were prepared in which preclinical studies (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) (Table 1) and clinical trials (24)(25)(26)(27)(28)(29)(30) (Table 2) were grouped.…”
Section: Resultsmentioning
confidence: 99%
“…Their results show that IN administration did not produce local structural damage (15,22,23) or outside the nasal cavity (15), nor hematological alterations (15,24,29) or serious adverse events, and was well tolerated by patients (24,26,29) . After IN administration, it reached the brain (11,12) and exerted neuroprotective effects in biomodels of cerebral ischemia (11,13,14,16,17) and Alzheimer's disease (18, 1 9) , as well as in patients with Parkinson's disease (25,26,27,29) , spinocerebellar ataxia type 2 (29) or Alzheimer's disease (30) . Neuroprotective effects were manifested by decreased neuronal mortality and damaged tissue (11,(13)(14)(15)(16)(17)(18)(19)(20)(21) , as well as improved functional integrity (11,13,14,(16)(17)(18)(19) .…”
Section: Discussionmentioning
confidence: 96%
“…Direct evidence of neuroEPO plus in the CNS has been demonstrated in Mongolian gerbils using radiolabeled neuroEPO plus [ 25 , 26 ]. Indirect evidence of neuroEPO plus in the cerebral spinal fluid (CSF) is supported by studies measuring total EPO in the CSF of non-human primates [ 26 ] and in patients with Spinocerebellar ataxia type 2 (SCA2) [ 27 ]. These studies suggest that neuroEPO plus is reaching the intended target when delivered intranasally.…”
Section: Introductionmentioning
confidence: 99%
“…NeuroEPO plus has been safely evaluated in healthy volunteers [ 28 ], patients with SCA2 [ 27 ] and patients with Parkinson disease [ 29 ]. We conducted a phase 2–3 trial (ATHENEA), to assess the safety and efficacy of neuroEPO plus in participants with mild-to-moderate Alzheimer’s clinical syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…Preclinical studies have demonstrated the effects of NeuroEPO on CNS protection in models of Alzheimer's, stroke, and glutamate-induced excitotoxicity (6)(7)(8)(9). In clinical studies, intranasal administration has shown to be safe and well tolerated in healthy volunteers and shows favorable effects with clinical improvement in patients with Parkinson's disease, Alzheimer's, and spinocerebellar ataxia type 2 (10)(11)(12)(13)(14). In addition, NeuroEPO has beneficial effects on glycemia and reproduction in diabetic rats.…”
Section: Introductionmentioning
confidence: 99%